2020
DOI: 10.1177/0017896920965992
|View full text |Cite
|
Sign up to set email alerts
|

Do text messages about health and development in young children affect caregiver behaviour and child outcomes? A systematic review

Abstract: Introduction: Inadequate caregiving conditions interfere with successful health and development outcomes. Access to appropriate information can result in improved health and development outcomes in children. Health promotion text messaging, a primary mHealth strategy, has been implemented in various countries to reach communities where the majority of the population may be living in poverty and lacks access to information and health services. This systematic review investigated what effect the provision of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…The mHealth training program for ECD practitioners provides a scalable, low-cost training for primary and secondary prevention of childhood hearing loss, especially in low-and middle-income countries and communities of low SES. Furthermore, the provision of training material via an instant-messaging application has important advantages, including cost-effective administration of an intervention program, efficient management, and easy distribution across geographic boundaries [ 28 , 41 , 42 ]. This study was the first of its kind to evaluate the use of an mHealth training program to support knowledge and awareness of hearing health [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mHealth training program for ECD practitioners provides a scalable, low-cost training for primary and secondary prevention of childhood hearing loss, especially in low-and middle-income countries and communities of low SES. Furthermore, the provision of training material via an instant-messaging application has important advantages, including cost-effective administration of an intervention program, efficient management, and easy distribution across geographic boundaries [ 28 , 41 , 42 ]. This study was the first of its kind to evaluate the use of an mHealth training program to support knowledge and awareness of hearing health [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Innovative mHealth approaches are rapidly becoming important for public health care in LMICs, providing tools for awareness, health promotion campaigns, and services that are accessible and can scale rapidly [ 20 , 23 , 24 , 25 , 26 , 27 , 28 ]. In addition, the ubiquity of mobile phones and increased internet access have created an opportunity to optimize the implementation of mHealth services and potentially increase the efficiency of various service-delivery cadres [ 18 , 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that social media interventions are more effective among disadvantaged populations such as youth, older adults, low-income people, and people residing in rural areas. Richardson et al [ 16 ] reported that SMS text messaging is an effective tool to influence caregiver behavior and child outcomes in health, whereas the results of the studies reviewed by Poorman et al [ 17 ] were mixed, and the authors concluded that SMS texting interventions that are based on an established theory of behavior change and use motivational language, as opposed to informational language, are more likely to be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Digital communication campaigns have been leveraged to improve nutrition and physical activity (PA), increase breastfeeding and immunization rates, reduce barriers to preventive health screenings, and improve access to mental health support [14][15][16][17]. Petkovic et al [14] reported that social media interventions designed to increase PA may be effective, and social media interventions may improve overall well-being.…”
Section: Introductionmentioning
confidence: 99%